Medial Patellofemoral Ligament Reconstruction Procedure Using a Suspensory Femoral Fixation System - Nakagawa, Shuji (Elsevier, 2013)
Recurrent patellar dislocation has recently been treated with anatomic medial patellofemoral ligament (MPFL) reconstruction using a semitendinosus muscle tendon. Although it is necessary to add tension to fix the tendon graft without loading excess stress on the patellofemoral joint, adjustment of the tension can be difficult. To resolve this problem, we developed an MPFL reconstruction procedure using the ToggleLoc Fixation Device (Biomet, Warsaw, IN), in which the semitendinosus muscle tendon is folded and used as a double-bundle tendon graft and 2 bone tunnels and 1 bone tunnel are made on the patellar and femoral sides, respectively. The patellar side of the tendon graft is fixed with an EndoButton (Smith & Nephew, London, England), and the femoral side is fixed with the ToggleLoc. Stepless adjustment of tension of the tendon graft is possible by reducing the size of the loop of the ToggleLoc hung onto the tendon graft. It may be useful to position the patella in the center of the femoral sulcus by confirming the patellofemoral joint fitting. Stability can be confirmed by loading lateral stress on the patella in the extended knee joint. This procedure is less invasive because opening of the lateral side of the femur is not necessary, and it may be useful for MPFL reconstruction.